The design of a model locomotive boiler / Md Shah Kassim - Kebing, Rowland; Kassim, Md. Shah (1985)
This report on a proposed model locomotive boiler suggested base on simple studies and experiment on the boiler and steam. Basic concept that govern the functioning, consturction and design of a model boiler are briefly discussed as a background to the project.